History teaching, History researched – Contributions of the Didactics of History and the History of Education to History Teaching in Brazil - Campos, Raquel Discini de; Alves, Ronaldo Cardoso [UNESP] (My University, 2024)
This article explores the teaching of History within a context of rapid technological transformations, automated teaching platforms, and the rise of far-right movements in Brazil and globally. It highlights the importance of teacher education that understands the Didactics of History as a field of knowledge stemming from Historical Science, as well as the History of Education as a body of knowledge that enables an understanding of the school culture in which teachers and students are embedded. It emphasizes that, amid the technological acceleration that immerses us in a kind of “continuous present, ” as classically foreseen by Hobsbawm (1995), teaching History becomes essential for promoting historical awareness and critical reflection on highly complex and sensitive topics. It posits that, through the use of varied historical sources and a reflective approach to didactics, teacher training programs should prepare professionals who act as autonomous builders of knowledge, integrating historical knowledge into everyday school life and expanding its reach through new forms of public engagement.
HISTÓRIA ENSINADA, HISTÓRIA PESQUISADA – contribuições da Didática da História e da História da Educação para o Ensino de História no Brasil
Keywords: Cultura Escolar; Didactics of History; Didática da História; Ensino de História; History Teaching; School Culture